2015
DOI: 10.1016/j.nbd.2015.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Vigabatrin therapy implicates neocortical high frequency oscillations in an animal model of infantile spasms

Abstract: Abnormal high frequency oscillations (HFOs) in EEG recordings are thought to be reflections of mechanisms responsible for focal seizure generation in the temporal lobe and neocortex. HFOs have also been recorded in patients and animal models of infantile spasms. If HFOs are important contributors to infantile spasms then anticonvulsant drugs that suppress these seizures should decrease the occurrence of HFOs. In experiments reported here, we used long-term video/EEG recordings with digital sampling rates capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 54 publications
4
31
0
Order By: Relevance
“…Hypsarrhythmia generated in the TTX model includes high-frequency oscillations that occur most commonly contralateral to the site of TTX infusion (37, 38). The TTX model has been reported to respond to vigabatrin treatment (39), but no studies of ACTH treatment have been published.…”
Section: Currently Available Rodent Models Of Infantile Spasmsmentioning
confidence: 99%
“…Hypsarrhythmia generated in the TTX model includes high-frequency oscillations that occur most commonly contralateral to the site of TTX infusion (37, 38). The TTX model has been reported to respond to vigabatrin treatment (39), but no studies of ACTH treatment have been published.…”
Section: Currently Available Rodent Models Of Infantile Spasmsmentioning
confidence: 99%
“…Short-term resolution of spasms and hypsarrhythmia is necessary, but clearly insufficient to guarantee an enduring response. Perhaps the key to sustained response without relapse is aggressive treatment beyond the resolution of spasms and hypsarrhythmia, with the goal of "correcting" a novel biomarker of epileptogenesis, such as the elimination of interictal HFOs, as suggested by a contemporary animal study 41 and a recent surgical series that included patients with infantile spasms. 39 A definitive evaluation of ZNS, TPM, or any other treatment for prevention of relapse is a challenging endeavor and will require a prospective, large-scale study with appropriate experimental controls.…”
Section: Epilepsia Ilaementioning
confidence: 99%
“…Frost and coworkers used the tetanus toxin model for infantile spams and showed a reduction of HFO following vigabatrin therapy. 60 A mesiotemporal lobe epilepsy model showed a reduction of HFO following treatment with lacosamide and neurosteriods. 61 , 62 The same group showed that treatment with levetiracetam directly after status epilepticus could reduce the likelihood of spontaneous seizures and that this was reflected in reduced rates of HFO in the treatment group.…”
Section: High Frequency Oscillations and Treatment Response To Anti-smentioning
confidence: 99%